Metaphors and Transfiguration: A. S. Byatt’s “Morpho Eugenia” and Philip Haas’s Angels and Insects - Séllei, Nóra (FOCUS: Papers in English Literary and Cultural Studies, 2024)
A. S. Byatt’s “Morpho Eugenia,” first published in 1992 in a volume also including “The Conjugial Angel” under the joint title of Angels and Insects, was, at an almost unimaginable speed, adapted to film by 1995. Directed by Philip Haas, music composed by Alexander Balanescu, and starring Mark Rylance, Kristin Scott Thomas, and Patsy Kensitt, the film version was given the title Angels and Insects. This great speed, to me, would suggest that there must be something special, perhaps even provokingly cinematic in Byatt’s text that invites a film adaptation. Whereas I maintain this claim, as a point of departure for my discussion of these literary and cinematic texts, f must make two personal statements: first, that out of the two, I had an encounter with the film first; second, that on reading the text 1 could hardly recognize the film and the text as “the same,” so much so that I started reading “The Conjugial Angel” in (a vain) search for further details that I thought I remembered from the film (this mistaken guess of mine can obviously be traced back to Haas’s change of title as well).